A NEW HALPERN-TYPE AVERAGING ALGORITHM WITH INERTIAL AND ERROR TERMS FOR FIXED POINTS OF ASYMPTOTICALLY NONEXPANSIVE MAPS. (2020) - NWOKORO, P.U.; OSILIKE, M.O.; AGBEBAKU, D.F.; CHIMA, E.E.; ONAH, A.C.
No abstract available